Makna ἐν Χριστῷ Menurut Paulus dalam Surat 2 Korintus 5:17 Bagi Orang Percaya - Tami Tami (Jurnal Teologi Cultivation, 2022)
Abstract:Phrase “It is in Christ (ἐν Χριστῷ)” appears a great many times in the New Testament especially in the books written by Paul. "It is in Christ" is no longer a foreign thing to Christianity today. So this becomes an important topic to be interpreted well; lived and lived earnestly in other words until it became an expression or lifestyle of a true Christian faith. For the significance of living faith is that which leads one to the knowledge of the true Jesus Christ that is; in His death, burial, and resurrection. And this is the saving faith. To be a follower of Jesus Christ is to continue the process of purifying oneself by the work of the Holy Spirit through baptism, repentance every day. From there it was later refined and became a new creation. The new creation in Jesus (ἐν Χριστῷ), that is, to leave "the old" (the old man) and "the new one has come" into the "new man". This new creation is closely related to a change in action, a change in mindset or a Christ-centered perspective. Just as it was Christ who became the center of life and came to life with Christ or achieved the theosis that was the purpose of God creating man.Abstrak:Frasa “berada di dalam Kristus (ἐν Χριστῷ)” ada banyak sekali muncul di dalam Perjanjian Baru khususnya dalam kitab-kitab yang ditulis oleh Paulus. “Ada di dalam Kristus” bukan lagi hal yang asing bagi Kekristenan dewasa ini. Sehingga ini menjadi suatu topik penting untuk dimaknai dengan baik; dihayati dan dihidupi dengan sungguh-sungguh dengan kata lain sampai menjadi sebuah ekpresi atau gaya kehidupan iman Kristen yang sejati. Karena signifikansi daripada iman yang hidup adalah iman yang menuntun seseorang pada pengenalan akan Yesus Kristus yang benar yaitu; di dalam kematian, penguburan, dan kebangkitan-Nya. Dan inilah iman yang menyelamatkan. Menjadi pengkut Yesus Kristus berarti terus berproses menyucikan diri oleh karya Roh Kudus melalui baptisan, pertobatan setiap hari. Dari situlah kemudian dilahirbarukan dan menjadi ciptaan baru. Ciptaan baru di dalam Yesus (ἐν Χριστῷ), yaitu meninggalkan “yang lama” (manusia lama) dan “yang baru sudah datang” menjadi “manusia baru”. Ciptaan baru ini berkaitan erat dengan perubahan tindakan, perubahan pola pikir (mindset) atau cara pandang yang berpusat pada Kristus. Sebagaimana Kristuslah yang menjadi pusat hidup dan manunggal dengan Kristus atau mencapai theosis itulah tujuan Allah menciptakan manusia.